2014
DOI: 10.5371/hp.2014.26.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term Results of Autologous Bone Marrow Transplantation in Osteonecrosis of the Femoral Head

Abstract: Purpose: This study evaluated mid-term clinical and radiological results of autologous bone marrow transplantation (BMT) for early stage osteonecrosis of the femoral head (ONFH) and analyzed prognostic factors. Materials and Methods: From November 2003 to April 2008, 101 hips of 93 patients with early stage ONFH who underwent autologous BMT were followed for at least five years. For clinical results, preoperative and postoperative Harris hip scores (HHS) were evaluated and survival rate was obtained at the poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Grafting of concentrated bone marrow mononuclear cells (BMMC) has been combined to core decompression to treat the early stage of ONFH, and several studies showed promising results. 91 92 93 94 95 96 97 Given that size and location of the necrotic lesion are the major determinants of further collapse of the femoral head and collapse does not occur in small lesions even without any intervention, 19 98 99 there is limited evidence to confirm the effectiveness of BMMC therapy in well-designed studies. Thus, a large-scale randomized controlled trial to verify the efficacy of core decompression with/without BMMC is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Grafting of concentrated bone marrow mononuclear cells (BMMC) has been combined to core decompression to treat the early stage of ONFH, and several studies showed promising results. 91 92 93 94 95 96 97 Given that size and location of the necrotic lesion are the major determinants of further collapse of the femoral head and collapse does not occur in small lesions even without any intervention, 19 98 99 there is limited evidence to confirm the effectiveness of BMMC therapy in well-designed studies. Thus, a large-scale randomized controlled trial to verify the efficacy of core decompression with/without BMMC is warranted.…”
Section: Discussionmentioning
confidence: 99%